2021
DOI: 10.1002/jcsm.12791
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise and nutritional interventions for augmenting sarcopenia outcomes in chronic kidney disease: a narrative review

Abstract: Sarcopenia is an age‐related progressive muscle disease characterized by loss of muscle mass, muscle strength and physical performance with high prevalence in chronic kidney disease (CKD). CKD is associated with decreased muscle protein synthesis and muscle breakdown due to a number of factors including, the uremic inflammatory environment of the disease. CKD patients are highly sedentary and at risk of malnutrition which may exacerbate sarcopenia outcomes even further. Short and long‐term exercise and nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 83 publications
1
22
0
1
Order By: Relevance
“…For example, patients with CKD who underwent RT and a nutritionist-supervised diet showed decreases in IL-6, emphasizing the importance of nutrition in these patients [ 49 ]. Adding nutritional behavioral changes (such as increasing protein intake) to exercise programs could help clinicians to slow down sarcopenia in CKD patients, although more studies are needed [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with CKD who underwent RT and a nutritionist-supervised diet showed decreases in IL-6, emphasizing the importance of nutrition in these patients [ 49 ]. Adding nutritional behavioral changes (such as increasing protein intake) to exercise programs could help clinicians to slow down sarcopenia in CKD patients, although more studies are needed [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to combining oral nutrition supplements with physical activity interventions, a narrative review reported that four trials of high-protein oral nutrition supplements combined with exercise demonstrated improvements in muscle strength and performance but not muscle mass [60]. The authors suggested that the combination of exercise and oral nutrition supplements is more effective than oral nutrition supplements alone [60].…”
Section: Treatment Approach For Sarcopenia and Sarcopenic Obesity In ...mentioning
confidence: 99%
“…bioelektische Impedanzanalyse (BIA): misst den Ernährungszustand und die Muskelmasse 6 , 20 , 29 , 30…”
Section: Physical Performance: Testen Messen Verfolgenunclassified